“Composure” and “wild fury”: Religious debates in the 17th-century English Catholic community - A. Yu. Seregina (Шаги)
Early Modern European culture abounded in various forms of public controversies. These included university debates, literary dialogues, printed polemical works, etc. The Reformation and the resulting confessional conflicts added numerous religious disputations. Religious disputations were closely linked to conversions to the ‘true faith’ and could be addressed to either national audiences or to relatively small groups. How were these ‘private disputations’ perceived and described by those who witnessed such events? In the 16th–17thcenturies the European audience was well versed in the arguments of both Catholic and Protestant theologians. What, then, could be considered a victory when almost every argument of the disputants was predictable? The article presents an analysis of a disputation narrative — the story of the debates between an Anglican divine, William Chillingworth, and a Jesuit, Thomas Holland, which were held in 1634 at the house of Elizabeth Cary, Viscountess Falkland. The disputation was organized to help persuade the daughters of Lady Falkland, newly converted Catholics and future nuns Anne, Lucy, Elizabeth and Mary Cary, who experienced a religious crisis. The disputation narrative was part of the biography of Lady Falkland written by her daughters. The story was closely connected to the narrative of the conversion of the mother and the daughters to Catholicism. The process was presented as an “intellectual conversion” through rational arguments. However, the story of the disputation focuses not on the arguments but on the behavior of all the participants, and on their emotions. This is a reflection of the views of the 17th-century polemicists regarding the role of emotions and passions in the process of religious conversion and the search for truth.